2015
DOI: 10.1134/s1560090415030094
|View full text |Cite
|
Sign up to set email alerts
|

Controlled radical copolymerization of styrene with acrylic acid and tert-butyl acrylate under conditions of reversible addition-fragmentation chain transfer: Control of the chain microstructure

Abstract: The copolymerization of styrene and acrylic acid and the copolymerization of styrene and tert butyl acrylate that are mediated by benzyl dithiobenzoate and dibenzyl trithiocarbonate as reversible addi tion fragmentation chain transfer agents are studied for the first time. It is shown that the copolymerization of these monomer pairs mediated by reversible addition fragmentation chain transfer agents occurs via the pseudoliving radical mechanism and is characterized by a linear increase in the number average mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 20 publications
(26 reference statements)
0
9
0
Order By: Relevance
“…Recently, we have shown that, in the RAFT copolymerization of polar-non-polar monomer pair, relative monomer reactivities could be adjusted not only by varying the polarity of the solvent, but also by governing the hydrophilicity/hydrophobicity of the polymeric RAFT agent. 59 The similar effect of the macroinitiator and the macromonomer on the relative monomer reactivities was also described for the case of the stable free radical polymerization 60 and for the conventional radical polymerization. 61 Hence, one can conclude that the similar effect of variations in the relative monomer reactivities is observed for the systems under study in the presence of Pol-A and Cop-H5.…”
Section: Copolymerization Of Butyl Acrylate and 223444-hexauoromentioning
confidence: 69%
“…Recently, we have shown that, in the RAFT copolymerization of polar-non-polar monomer pair, relative monomer reactivities could be adjusted not only by varying the polarity of the solvent, but also by governing the hydrophilicity/hydrophobicity of the polymeric RAFT agent. 59 The similar effect of the macroinitiator and the macromonomer on the relative monomer reactivities was also described for the case of the stable free radical polymerization 60 and for the conventional radical polymerization. 61 Hence, one can conclude that the similar effect of variations in the relative monomer reactivities is observed for the systems under study in the presence of Pol-A and Cop-H5.…”
Section: Copolymerization Of Butyl Acrylate and 223444-hexauoromentioning
confidence: 69%
“…For example, if we compare the copolymer prepared via copolymerization in bulk and in DMF in the presence of BDB, we find that the former is more enriched with AA units. 38 This may come from the solvent-induced dissociation of the dimers of carboxylic acids and the formation of H-complexes of DMF and AA, which leads to a decrease in AA reactivity. Another factor related to the effect of preferential solvation is when the polar monomer (AA) is replaced by the polar solvent from the macromolecular coil.…”
Section: Resultsmentioning
confidence: 99%
“…Solvent effect (copolymerization in bulk) also has an influence on the relative monomer activities. 38 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The carboxylic acids in the A block self-associate strongly through the hydrogen-bond interaction. In addition, the copolymerization of this pair is well-studied in detail, , including modern living polymerization schemes, both RAFT , and NMP. , …”
Section: Introductionmentioning
confidence: 99%